Aproximações interdisciplinares entre o ensino da matemática e a literatura infantil: uma aprendizagem significativa - Ghelli, Kelma Gomes Mendonça (2019)
This survey aims to answer the following problem: What are the obstacles to effective interdisciplinary practice and how to break with traditional practices in teaching Mathematics and Children's Literature? So, this thesis intended to present methodological possibilities through an interdisciplinary work articulating teaching of Mathematics and Children's Literature. For that, we carried out a theoretical bibliographic study which describes and analyze the main questions concerned to the act of teaching and learning Mathematics. We made a theoretical deepening on Ausubel’s Theory of Significant Learning. We also discussed the initial and continuing teacher training and the teachers’ conceptions on the process of teaching and learning Mathematics and analyzed some alternatives that can contribute to the improvement of Mathematics teaching through Children's Literature. The results showed that the interdisciplinary approaches between the teaching of Mathematics and Children's Literature have much to contribute to the teacher’s pedagogical practice and to the student’s learning process. Integrating literature to Mathematics classes may render the teaching-learning process more attractive and innovative for both students and teachers Keywords: Children Literature. Significant Learning. Mathematics.